О некоторых пищеварительных ферментах паутинного клеща Tetranychus cinnabarinus Воisduval (Tetranychoidea) - Барабанова, В.В. (Вестник зоологии, 1972)
The article deals with studying optimal conditions of total proteolytic activity of amylase in Tetranychus cinnabarinus as well as specificity of these mites'amylase effect on starches of potato and Nufar luteum (L.) — atypical fodder plant for them. Optimal values for proteases were 4.0, for amylase— 5.5. Optimal temperature for proteases was 30-35° C. For amylases the temperatures up to 50° C were not optimal. The mites can eat Nufar luteum — an atypical fodder plant for them and normally develop on it. Amylase of the mites attacks the starch of this plant not much less than potato starch. Absence of T. cinnabarinus on Nufar luteum in nature may be explained by conditions of this plant wintering unsuitable for mites.